Analysis of Strength & Weakness, Using the Concept of Resource-Based View with the VRIO Framework in Sharia Cooperatives - Prasetio Ariwibowo; Firdaus Budhy Saputro; Haryanto Haryanto (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2021)
This type of research used in this study is a qualitative research method. Determination of respondents is done by means of Non Probability sampling (purposive sampling). The Resource-based View of the Firm approach to test data analysis in this study aims to determine the potential of internal resources that differentiate one BMT / other sharia cooperative from other BMT / sharia cooperatives, which can make one BMT / other sharia cooperative be superior to that. another. Findings. (There are criteria that can be used to determine whether a resource has a competitive advantage or not. In an industry there must be BMT / sharia cooperatives that are superior, becoming market leaders compared to other sharia BMT / cooperatives even though they all face the same external environment, it can be seen that the internal environment is what differentiates one BMT / other sharia cooperatives from BMT / Another sharia cooperative, which can make one BMT / other sharia cooperative be superior to the others. So that, the conditions of financial institutions can be used by stakeholders and stockholders to evaluate the performance of financial institutions in applying the principles of prudence, compliance with applicable regulations, and risk management.